HUKUM KOMUNIKASI SEBAGAI PERTEMUAN HUKUM, MEDIA, DAN TEKNOLOGI INFORMASI: ANALISIS KAJIAN PUSTAKA ATAS NORMA‑NORMA YANG MENGATUR PROSES PENYAMPAIAN PESAN SECARA LANGSUNG DAN DARING - Gunawan Widjaja (Jurnal Komunikasi, 2026)
Communication law, as the intersection of law, media, and information technology, is a crucial domain in maintaining the balance between freedom of expression and the protection of rights to honour, dignity, and privacy in the digital age. This article examines the norms governing the process of direct and online message delivery, focusing on two main discussions: (1) legal norms in direct communication contained in the Criminal Code, the Civil Code, and regulations related to human rights, and (2) regulations and challenges of online communication in the digital era as supported by the Electronic Information and Transaction Law (ITE Law), the Personal Data Protection Law, and various derivative regulations. The results of the study show that communication law must be developed in an adaptive and principle-based manner, integrating the revision of norms, institutional strengthening, digital literacy education, and international cooperation so that the communication space—both direct and online—becomes a safe, fair, and responsible space for all actors.